ANALISIS KEMAMPUAN BERNAVIGASI GUNA MENINGKATKAN KESELAMATAN PELAYARAN DI MV. SOPHIA - Arham Herman; Welem Ada; Ade Chandra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the navigational competence of watchkeeping officers in enhancing maritime safety on board MV. Sophia, focusing on a Global Positioning System (GPS) disturbance that occurred during rainfall on 3 December 2024 while the vessel was sailing in waters near Dubai. A qualitative descriptive method with a case study approach was employed. Data were obtained through direct observation, structured interviews with the Chief, Second, and Third Officers, and documentation review. The findings show that the GPS disturbance produced unstable and inaccurate position readings for approximately one hour during each of two separate rainfall periods, yet the watchkeeping officers maintained safe navigation by cross-checking position data using radar, ECDIS, AIS, and visual observation, consistent with the principles set out in SOLAS Chapter V and STCW 1978 as amended. The study concludes that navigational competence, particularly the ability to avoid dependence on a single instrument, plays a decisive role in preventing maritime accidents during electronic navigation system disturbances. Continued training in cross-checking procedures and a stronger understanding of equipment limitations are recommended.